Transcriptomic evidence for immaturity induced by antidepressant fluoxetine in the hippocampus and prefrontal cortex. Issue 2 (16th February 2019) - Hagihara, Hideo; Ohira, Koji; Miyakawa, Tsuyoshi
Abstract: Aims: The molecular and cellular mechanisms underlying the antidepressant effects of fluoxetine in the brain are not fully understood. Emerging evidence has led to the hypothesis that chronic fluoxetine treatment induces dematuration of certain types of mature neurons in rodents. These studies have focused on the properties of typical molecular and/or electrophysiological markers for neuronal maturation. Nevertheless, it remains unknown whether dematuration‐related phenomena are present at the genome‐wide gene expression level. Methods: Based on the aforementioned hypothesis, we directly compared transcriptome data between fluoxetine‐treated adult mice and those of naive infants in the hippocampus and medial prefrontal cortex (mPFC) to assess similarities and/or differences. We further investigated whether fluoxetine treatment caused dematuration in these brain regions in a hypothesis‐free manner using a weighted gene co‐expression network analysis (WGCNA). Results: Gene expression patterns in fluoxetine‐treated mice resembled those in infants in the mPFC and, to a large extent, in the hippocampus. The gene expression patterns of fluoxetine‐treated adult mice were more similar to those of approximately 2‐week‐old infants than those of older mice. WGCNA confirmed that fluoxetine treatment was associated with maturation abnormalities, particularly in the hippocampus, and highlighted respective co‐expression modules for maturity and immaturity marker genes in the hippocampus in response to fluoxetine treatment. Conclusions: Our results strongly support the hypothesis that chronic fluoxetine treatment induces dematuration in the adult mouse brain from a transcriptomic standpoint. Detection of discrete transcriptomic regulatory networks related to fluoxetine treatment may help to further elucidate the mechanisms of antidepressant action. Abstract : This study compares the transcriptomic profile of adult mice treated with clinically relevant dose of FLX and that of naïve infants in the hippocampus and medial prefrontal cortex (mPFC). We observed that gene expression profiles in FLX‐treated adult mice resembled those of infants in the mPFC and hippocampus. Our results provide support for the hypothesis that FLX can cause dematuration of the adult mouse brain to a more immature phenotype.